2017
DOI: 10.3847/1538-3881/aa6a15
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Hα Transits for HD 189733 b: Stellar Activity versus Absorption in the Extended Atmosphere

Abstract: HD 189733 b is one of the most well-studied exoplanets due to its large transit depth and host star brightness. The focus on this object has produced a number of high-cadence transit observations using high-resolution optical spectrographs. Here we present an analysis of seven full Hα transits of HD 189733 b using HARPS on the 3.6 meter La Silla telescope and HIRES on Keck I, taken over the course of nine years from 2006 to 2015. Hα transmission signals are analyzed as a function of the stellar activity level,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 105 publications
(197 reference statements)
6
50
0
Order By: Relevance
“…This is because the extended atmosphere of neutral hydrogen becomes almost entirely in the ground state at older ages. Our result agrees with the lack of absorption observed in the Hα transits of GJ436b (Cauley et al 2017), in spite of its impressively long and extended transit in Lyα (Kulow et al 2014;Ehrenreich et al 2015;Lavie et al 2017). This situation can occur when temperatures are not high enough to excite hydrogen.…”
Section: Hα Transitssupporting
confidence: 91%
“…This is because the extended atmosphere of neutral hydrogen becomes almost entirely in the ground state at older ages. Our result agrees with the lack of absorption observed in the Hα transits of GJ436b (Cauley et al 2017), in spite of its impressively long and extended transit in Lyα (Kulow et al 2014;Ehrenreich et al 2015;Lavie et al 2017). This situation can occur when temperatures are not high enough to excite hydrogen.…”
Section: Hα Transitssupporting
confidence: 91%
“…Cauley et al (2018) showed for HD189733b that the transit of active latitudes with bright facular and plage regions can cause emission feature in stellar lines. Also the strong magnetic field of HD189733 could have a significant effect on the emission in lines (Cauley et al 2017). Possibly related to the activity, we see an emissionlike feature in several stellar line cores as e.g.…”
Section: Stellar Activity Of Hd189733mentioning
confidence: 67%
“…Gray (Gray & Corbally 1994). For the calculation of the model atmospheres we used the Kurucz model (Kurucz 1970;Castelli & Kurucz 2004). For HD189733b, we used an effective temperature of 4875 K, a surface gravity of log g = 4.56 and a metallicity of dex -0.03.…”
Section: Center-to-limb Variationmentioning
confidence: 99%
“…Transit absorption in the Hα line was also detected in several observations, as well as a pre-transit signature (Jensen et al 2012;Cauley et al 2015Cauley et al , 2016Cauley et al , 2017b. However, both in-and pre-transit absorption signatures were highly variable in time and strongly affected by stellar activity, making their interpretation difficult (Barnes et al 2016;Cauley et al 2017a;Kohl et al 2018). Furthermore, a 6-8% transit absorption in Xrays was reported by Poppenhaeger et al (2013), but more observations with higher sensitivity are needed to confirm this result (Marin & Grosso 2017).…”
Section: Introductionmentioning
confidence: 92%